Comparison of Hematoma Block V. Intravenous Sedation in Reduction of Distal Radius Extra Articular Fractures in Adults - Jahan Zeb Khan, Muhammad Omer Cheema, Muhammad Ammar Naqvi, Usman Latif, M. Saif-ur-Rehman, Zahid Shafiq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare hematoma block versus intravenous sedation in reduction of distal radius extra articular fractures in adults. Study Design: Randomized controlled trial. Place and Duration of the Study: The emergency department of Orthopedic Unit, Services Hospital, Lahore, Pakistan from 1st August 2021 to 31st January 2022. Material and Methods: A total of 330 patients who presented in the emergency department of Orthopedic Unit were included. Patients were divided into two groups (165 patients in each group). Patients in Group-A underwent hematoma block method (10ml of 2% lidocaine into the fracture site) while in Group-B, sedation method (using Inj. Propofol, 1-2.5mg induction and 50-200mcg/kg/min intravenous maintenance dose) was adopted. Pre reduction and post reduction pain scores were calculated using VAS from 0 (no pain) to 10 (severe pain). Details were recorded regarding age, gender of the patient, pain score and reduction time. Results: In a total of 330 cases, 91 (27.6%) were male and 239 (72.4%) were female. Overall, mean age was calculated to 35.22±8.81 years while 224 (67.9%) patients were aged between 20 to 40 years. Mean pain score was calculated to be 4.96±0.74 before the treatment. Post-treatment, patients in hematoma block method group had statistically significant less pain score (p=0.0001), total reduction in pain (p=0.0002) and time to reduction of pain (p=0.0001). Conclusion: We concluded that hematoma block is superior in terms of mean reduction in pain score and mean time to reduction in patients presenting with distal radial fractures when compared with intra-venous sedation.